Self-hole-sealing and self-healing aluminum alloy corrosion-resistant coating and preparation method thereof

By using cerium ions-containing phosphate electrolyte on the surface of the aluminum alloy for microarc oxidation treatment, a self-sealing and self-healing microarc oxidation coating is formed, which solves the problems of poor sealing effect and complex process of aluminum alloy microarc oxidation coating in the prior art, and achieves efficient corrosion resistance and simplified processes.

CN119776942AActive Publication Date: 2025-04-08SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202510032499.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-08
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing aluminum alloy microarc oxidation coating has poor sealing effect and complex process, which leads to easy corrosion in actual environment.

Method used

The microarc oxidation treatment is performed on the surface of the aluminum alloy, and the phosphate electrolyte containing cerium ions is used to perform microarc oxidation treatment in a constant current mode through an AC power supply to form a self-sealing and self-healing microarc oxidation coating.

Benefits of technology

The self-sealing and self-healing effect of aluminum alloy surface is achieved, corrosion resistance is improved, process flow is simplified, and long-term active corrosion protection is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776942A_ABST
    Figure CN119776942A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal material surface treatment, and provides a self-hole-sealing and self-healing aluminum alloy corrosion-resistant coating and a preparation method thereof. The aluminum alloy is subjected to micro-arc oxidation treatment in the phosphate electrolyte containing cerium ions, the self-hole-sealing and self-healing micro-arc oxidation coating is prepared on the surface of the aluminum alloy, and the technical problems that in the prior art, an aluminum alloy micro-arc oxidation coating is poor in hole sealing effect and complex in process are solved. The beneficial effects of providing long-term active corrosion protection for the aluminum alloy and simplifying the process are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a self-sealing and self-healing aluminum alloy corrosion-resistant coating and a preparation method thereof. Background Art

[0002] Aluminum alloys are widely used in aerospace, marine equipment, automobiles, and 3C electronic components due to their low density, high strength, and easy processing. However, aluminum alloy parts are prone to corrosion when they are directly in service in actual environmental media, which limits their application. At present, micro-arc oxidation coatings are usually prepared on the surface of aluminum alloys to improve the corrosion resistance of aluminum alloys. However, the growth behavior of micro-arc oxidation coatings leads to a large number of holes on the surface. When used for a long time, the corrosive medium can easily penetrate the coating along the holes to reach the substrate and cause local corrosion. Therefore, it is critical to treat the weak holes on the surface of the micro-arc oxidation coating to improve its corrosion resistance.

[0003] In the prior art, secondary sealing technology is usually adopted to effectively alleviate or prevent the corrosion medium from penetrating along the pores, thereby improving the corrosion resistance of the micro-arc oxidation coating. Among them, organic sealing is to combine organic matter on the surface of the micro-arc oxidation coating by coating to completely cover the holes, but the organic and inorganic coatings are only physically combined, which can easily cause the coating to fall off, and the organic matter is prone to aging and failure after long-term service. Nanoparticle sealing is to use aluminum alloy to grow a coating in a micro-arc oxidation electrolyte containing nanoparticles to achieve the aggregation and blocking of nanoparticles at the hole position, but nanoparticles are easy to aggregate and precipitate in the electrolyte, resulting in poor sealing effect, and usually requires additional particle surface charge modification, and the process is complicated.

[0004] The present invention prepares a self-sealing and self-healing micro-arc oxidation coating on the surface of the aluminum alloy by subjecting the aluminum alloy to micro-arc oxidation in a phosphate electrolyte containing cerium ions. The preparation method provided by the present invention is simple in process, and the prepared coating has the technical effects of corrosion resistance, self-sealing and self-healing, which solves the technical problems of poor sealing effect and complex process of aluminum alloy micro-arc oxidation coating in the prior art. Summary of the invention

[0005] The present invention provides a self-sealing and self-healing aluminum alloy corrosion-resistant coating and a preparation method thereof, which are used to solve the defects of the prior art that the aluminum alloy is easy to corrode, the micro-arc oxidation coating has a poor sealing effect and a complicated process.

[0006] On the one hand, the present invention provides a method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating, taking an aluminum alloy as a substrate, placing the aluminum alloy substrate in an electrolyte for micro-arc oxidation treatment; the electrolyte includes phosphate, sodium hydroxide, disodium ethylenediaminetetraacetic acid and a soluble cerium salt.

[0007] According to the method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the concentration of the phosphate is 3-20 g·L -1 , the concentration of sodium hydroxide is 1~10g·L -1 , the concentration of disodium EDTA is 2~10g·L -1 , the concentration of soluble cerium salt is 1~20g·L -1 .

[0008] According to a method for preparing a self-sealing, self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the phosphate includes at least one of sodium hexametaphosphate, sodium pyrophosphate, sodium dihydrogen phosphate and sodium tripolyphosphate.

[0009] According to a method for preparing a self-sealing, self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the soluble cerium salt includes at least one of cerium nitrate, cerium acetate and cerium carbonate.

[0010] According to a method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the aluminum alloy substrate is any one of a 2-series aluminum alloy, a 5-series aluminum alloy, a 6-series aluminum alloy and a 7-series aluminum alloy.

[0011] According to a method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the micro-arc oxidation treatment is operated in a constant current mode using an AC power supply, the aluminum alloy substrate is used as an anode, and the stainless steel electrolytic cell is used as a cathode.

[0012] According to the method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the power of the AC power supply is 10-100 kW, and the current density is 2-10 A·dm -2 , frequency is 200~1000Hz, duty cycle is 10~30%, and discharge time is 5~20 minutes; the temperature of the electrolyte during the micro-arc oxidation treatment is 35~45°C.

[0013] According to a method for preparing a self-sealing, self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the preparation method also includes pre-treating the aluminum alloy substrate, and the pre-treatment is surface polishing and cleaning in sequence.

[0014] According to a method for preparing a self-sealing, self-healing aluminum alloy corrosion-resistant coating provided by the present invention, the cleaning is carried out under ultrasonic conditions, and the ultrasonic time is 5 to 15 minutes; the cleaning is carried out using deionized water and anhydrous ethanol in sequence.

[0015] On the other hand, the present invention provides a self-sealing, self-healing aluminum alloy corrosion-resistant coating.

[0016] The self-sealing and self-healing aluminum alloy corrosion-resistant coating and preparation method thereof provided by the present invention prepare a self-sealing and self-healing micro-arc oxidation coating on the surface of the aluminum alloy by subjecting the aluminum alloy to micro-arc oxidation treatment in a phosphate electrolyte containing cerium ions, thereby solving the technical problems of poor sealing effect and complex process of aluminum alloy micro-arc oxidation coating in the prior art, and achieving the beneficial effects of providing long-term active corrosion protection for the aluminum alloy and simplifying the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a self-healing principle diagram of the self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by an embodiment of the present invention; Figure 2 1 is a discharge curve diagram of Examples 1 to 3 of the present invention and Comparative Example 1 when preparing the coating; Figure 3 1 is a SEM image of the coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 4 LCSM images of the coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 5 It is a Tafel curve diagram of electrochemical testing of Examples 1 to 3 of the present invention, Comparative Example 1 and 2A12 aluminum alloy in 3.5wt.% NaCl solution; Figure 6 It is an EDS surface scan of the interior of the scratch of the coating prepared in Example 2 of the present invention and Comparative Example 1; Figure 7 It is an EDS line scan image of the interior of the scratches of the coatings prepared in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The invention provides a method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating. The aluminum alloy is used as a substrate, and the aluminum alloy substrate is placed in an electrolyte for micro-arc oxidation treatment; the electrolyte comprises phosphate, sodium hydroxide, disodium ethylenediaminetetraacetic acid and a soluble cerium salt.

[0021] In the present invention, the concentration of the phosphate is 3-20 g·L -1 , preferably 11~18g·L -1 , more preferably 14~16g·L -1 ; The concentration of sodium hydroxide is 1~10g·L -1 , preferably 2~8g·L -1 , more preferably 4~6g·L -1 ; The concentration of disodium EDTA is 2~10g·L -1 , preferably 3~8g·L -1 , more preferably 4~6g·L -1 ; The concentration of soluble cerium salt is 1~20g·L -1 , preferably 5~18g·L -1 , more preferably 8~15g·L -1 .

[0022] In the present invention, the phosphate includes at least one of sodium hexametaphosphate, sodium pyrophosphate, sodium dihydrogen phosphate and sodium tripolyphosphate, preferably sodium hexametaphosphate or sodium dihydrogen phosphate, and more preferably sodium hexametaphosphate.

[0023] In the present invention, the soluble cerium salt includes at least one of cerium nitrate, cerium acetate and cerium carbonate, preferably cerium nitrate or cerium acetate, and more preferably cerium acetate.

[0024] In the present invention, the aluminum alloy matrix is ​​any one of 2 series aluminum alloy, 5 series aluminum alloy, 6 series aluminum alloy and 7 series aluminum alloy, preferably 2 series aluminum alloy, and more preferably 2A12 aluminum alloy.

[0025] In the present invention, the micro-arc oxidation treatment is operated in a constant current mode using an alternating current power supply, with the aluminum alloy substrate serving as the anode and the stainless steel electrolytic cell serving as the cathode.

[0026] In the present invention, the power of the AC power source is 10-100 kW, preferably 12-50 kW, and more preferably 15-20 kW; the current density is 2-10 A·dm -2 , preferably 3~8A·dm -2 , more preferably 4~6A·dm -2; The frequency is 200~1000Hz, preferably 300~700Hz, and more preferably 400~600Hz; the duty cycle is 10~30%, preferably 12~20%, and more preferably 14~16%; the discharge time is 5~20 minutes, preferably 8~18 minutes, and more preferably 10~15 minutes; the temperature of the electrolyte during the micro-arc oxidation treatment is 35~45°C.

[0027] In the present invention, the preparation method further comprises pre-treating the aluminum alloy substrate, wherein the pre-treatment comprises surface polishing and cleaning in sequence.

[0028] In the present invention, the cleaning is carried out under ultrasonic conditions, the ultrasonic time is 5 to 15 minutes, preferably 8 to 12 minutes, and more preferably 10 minutes; the cleaning is carried out using deionized water and anhydrous ethanol in sequence.

[0029] The invention also provides a self-sealing and self-healing aluminum alloy corrosion-resistant coating.

[0030] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0031] Example 1 The 2A12 aluminum alloy was cut into samples of 50 mm × 25 mm × 1 mm, and the surface of the aluminum alloy sample was polished with 2000-grit sandpaper, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 10 minutes to obtain an aluminum alloy matrix. Sodium hexametaphosphate, sodium hydroxide, disodium ethylenediaminetetraacetate, and cerium acetate were added to deionized water in sequence to prepare a sodium hexametaphosphate concentration of 15 g·L -1 , the concentration of sodium hydroxide is 5g·L -1 , the concentration of disodium EDTA is 5 g·L -1 , the concentration of cerium acetate is 5 g·L -1 The surface of the aluminum alloy substrate was subjected to micro-arc oxidation in a constant current mode using a 15kW AC power supply micro-arc oxidation device. The aluminum alloy substrate was used as the anode, the stainless steel electrolytic cell was used as the cathode, and the current density was controlled to be 5A·dm -2 , frequency is 500Hz, duty cycle is 15%, discharge time is 10 minutes, and self-sealing and self-healing aluminum alloy corrosion-resistant coating is obtained. Circulating water is used in the micro-arc oxidation process to ensure that the temperature of the electrolyte is at 35~45℃ to prevent the arc temperature from being too high and causing ablation of the coating.

[0032] Example 2 The 2A12 aluminum alloy was cut into samples of 50 mm × 25 mm × 1 mm, and the surface of the aluminum alloy sample was polished with 2000-grit sandpaper, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 10 minutes to obtain an aluminum alloy matrix. Sodium hexametaphosphate, sodium hydroxide, disodium ethylenediaminetetraacetate, and cerium acetate were added to deionized water in sequence to prepare a sodium hexametaphosphate concentration of 15 g·L -1 , the concentration of sodium hydroxide is 5g·L -1 , the concentration of disodium EDTA is 5 g·L -1 , the concentration of cerium acetate is 10 g·L -1 The surface of the aluminum alloy substrate was subjected to micro-arc oxidation in a constant current mode using a 15kW AC power supply micro-arc oxidation device. The aluminum alloy substrate was used as the anode, the stainless steel electrolytic cell was used as the cathode, and the current density was controlled to be 5A·dm -2 , frequency is 500Hz, duty cycle is 15%, discharge time is 10 minutes, and self-sealing and self-healing aluminum alloy corrosion-resistant coating is obtained. Circulating water is used in the micro-arc oxidation process to ensure that the temperature of the electrolyte is at 35~45℃ to prevent the arc temperature from being too high and causing ablation of the coating.

[0033] Example 3 The 2A12 aluminum alloy was cut into samples of 50 mm × 25 mm × 1 mm, and the surface of the aluminum alloy sample was polished with 2000-grit sandpaper, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 10 minutes to obtain an aluminum alloy matrix. Sodium hexametaphosphate, sodium hydroxide, disodium ethylenediaminetetraacetate, and cerium acetate were added to deionized water in sequence to prepare a sodium hexametaphosphate concentration of 15 g·L -1 , the concentration of sodium hydroxide is 5g·L -1 , the concentration of disodium EDTA is 5 g·L -1 , the concentration of cerium acetate is 15 g·L -1 The surface of the aluminum alloy substrate was subjected to micro-arc oxidation in a constant current mode using a 15kW AC power supply micro-arc oxidation device. The aluminum alloy substrate was used as the anode, the stainless steel electrolytic cell was used as the cathode, and the current density was controlled to be 5A·dm -2 , frequency is 500Hz, duty cycle is 15%, discharge time is 10 minutes, and self-sealing and self-healing aluminum alloy corrosion-resistant coating is obtained. Circulating water is used in the micro-arc oxidation process to ensure that the temperature of the electrolyte is at 35~45℃ to prevent the arc temperature from being too high and causing ablation of the coating.

[0034] Comparative Example 1 The 2A12 aluminum alloy was cut into samples of 50 mm × 25 mm × 1 mm, and the surface of the aluminum alloy sample was polished with 2000-grit sandpaper, and then ultrasonically cleaned with deionized water and anhydrous ethanol for 10 minutes to obtain an aluminum alloy matrix. Sodium hexametaphosphate, sodium hydroxide, disodium ethylenediaminetetraacetate, and cerium acetate were added to deionized water in sequence to prepare a sodium hexametaphosphate concentration of 15 g·L -1 , the concentration of sodium hydroxide is 5g·L -1 , the concentration of disodium EDTA is 5 g·L -1 The surface of the aluminum alloy substrate was subjected to micro-arc oxidation in a constant current mode using a 15kW AC power supply micro-arc oxidation device. The aluminum alloy substrate was used as the anode, the stainless steel electrolytic cell was used as the cathode, and the current density was controlled to be 5A·dm -2 , frequency is 500Hz, duty cycle is 15%, discharge time is 10 minutes, and micro-arc oxidation coating is obtained. Circulating water is used in the micro-arc oxidation process to ensure that the temperature of the electrolyte is at 35~45℃ to prevent the arc temperature from being too high and causing ablation of the coating.

[0035] Combine the following Figure 1 to Figure 7 The invention describes a self-sealing, self-healing aluminum alloy corrosion-resistant coating and a preparation method thereof.

[0036] Figure 1 It is a self-healing principle diagram of the self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by an embodiment of the present invention.

[0037] like Figure 1 As shown, in comparative example 1, Ce is not doped, and Cl in the corrosion medium - It is difficult to corrode the Al2O3 coating body, but it is easy to penetrate the coating along the pores on the coating surface and inside to reach the substrate interface, thereby causing anodic dissolution corrosion of the aluminum alloy substrate at the interface.

[0038] Anode: Al→Al 3+ +3e - ; Cathode: O2+2H2O+4e - →4OH - .

[0039] Al generated at the corrosion interface 3+ With OH - It will react quickly to produce corrosion products Al(OH)3 and deposit on the corroded surface. At the same time, the corrosion product Al(OH)3 is not stable and will be oxidized by Cl in the corrosive medium. - Corrosion further forms loose corrosion products Al(OH) 3-n Cl n (n=1, 2, 3), reaction formula: Al 3++3OH - →Al(OH)3; Al(OH)3+nCl - →Al(OH) 3-n Cl n +nOH - , n=1,2,3.

[0040] Loose corrosion products have no protective effect, so the local corrosion position becomes a local weak point. With the immersion corrosion process, the formation of local pitting pits is accelerated, and eventually the micro-arc oxidation coating fails.

[0041] For the Ce-doped micro-arc oxidation coatings in Examples 1 to 3, the in-situ grown cerium phosphate and alumina form a mixed melt that fills the inside of the pores on the surface, forming a self-sealing effect, which effectively hinders the penetration of the corrosive medium along the pores to the coating / substrate interface. The cerium phosphate grown inside the coating is mainly in the form of nanocrystals that are wrapped by amorphous materials and evenly distributed throughout the alumina coating. During the long-term corrosion process of the coating, it is inevitable that the corrosive medium will partially penetrate to the coating / substrate interface and undergo the above-mentioned reaction. The Al(OH)3 generated by the corrosion will also be oxidized by Cl - Further dissolution forms a corrosion micro-area, and the cerium phosphate in the nearby coating is easily dissolved into Ce in this process. 3+ ions, and generate low Ksp corrosion product Ce(OH)3 at a faster rate, reaction formula: Ce 3+ +3OH - →Ce(OH)3.

[0042] Generally, loose Al(OH)3 single corrosion product cannot effectively prevent Cl - However, the Ce(OH)3 deposited with Ksp enhances the compactness of Al(OH)3, forming a mixed corrosion product layer of Al(OH)3 / Ce(OH)3, which effectively prevents the corrosion of Cl - The self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present invention thus exhibits self-healing properties, effectively slowing down the failure of the coating due to local corrosion, and greatly improving the long-term corrosion protection performance of the aluminum alloy substrate.

[0043] Figure 2 It is a discharge curve diagram of Examples 1 to 3 of the present invention and Comparative Example 1 when preparing micro-arc oxidation coatings.

[0044] like Figure 2As shown in the figure, the discharge curve can be divided into three stages. The first stage is the surface passivation stage (0~60s), the second stage is the passivation layer breakdown discharge stage (60~300s), and the third stage is the rapid and stable growth stage of the micro-arc oxidation coating (300~600s). In the first 0~60s, the aluminum alloy forms a dense Al2O3 passivation layer by matrix oxidation reaction under the action of current in the phosphate electrolyte, so the voltage of the sample rises very rapidly. And with the increase of the Ce salt content, the voltage increases faster. This is because more Ce salt reduces the free path of ion movement in the solution, and the conductivity of the phosphate electrolyte decreases, so the passivation voltage of the coating is higher. When the voltage continues to rise to the breakdown voltage of the Al2O3 passivation layer, a large amount of charge accumulated on the surface begins to be released, similar to the discharge stage of the capacitor, and enters the passivation layer breakdown discharge stage (60~300s). The surface voltage of the sample gradually increases, and the higher the Ce salt content, the greater the voltage increase, which is consistent with the evolution law of the initial passivation stage. At this stage, as the voltage increases, the insulating passivation layer on the sample surface grows slowly, and the arc formed breaks through the Al2O3 passivation layer to form a discharge channel. The matrix aluminum melts and sprays out and contacts the electrolyte to produce a chemical reaction or plasma reaction, thereby generating aluminum oxide and aluminum metal salt. At the same time, the high temperature in the discharge channel promotes the Ce ions and PO4 3- The reaction generates Ce phosphate and melts inside the hole. After 300s, the micro-arc oxidation coating enters a rapid and stable growth stage. At this time, the discharge voltage of the coating keeps a gradual upward trend, and the arc discharge process becomes intense. The higher the Ce salt content, the greater the resistance of the coating and the more obvious the voltage increase. As the discharge process continues to start and end, the coating gradually grows and eventually forms a complex mixture phase. Since the arc on the coating surface becomes huge due to the high voltage after 600s, continuous breakdown arcs will occur locally, causing coating ablation, so the micro-arc oxidation discharge process is terminated to obtain the final micro-arc oxidation coating.

[0045] Figure 3 3 are SEM images of the coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1.

[0046] like Figure 3 As shown, Figure 3 (a) is comparative example 1, Figure 3 (b) is Example 1, Figure 3 (c) is Example 2, Figure 3(d) is Example 3. It can be seen that the surfaces of the micro-arc oxidation coatings of Examples 1 to 3 and Comparative Example 1 all show a typical porous structure. The edges of the holes are all crater-like in shape. This is because the discharge behavior is very similar to the volcanic eruption process, and the molten material formed will accumulate at the mouth of the hole. However, it is obvious that the holes of the coatings doped with different contents of Ce salts are very different, and their hole distribution and pore size are significantly different. The holes in Comparative Example 1 are densely distributed and have a small pore size. In addition to some large pores larger than 5 μm, there are many dense nanopores nearby. This is because the growth voltage of the undoped micro-arc oxidation coating is small, and the main phase of the coating is only Al2O3. At the same voltage, it is less difficult for the coating to be broken down, and the overall arc density increases, so a prosperous and dense small-sized arc discharge phenomenon will be formed. In contrast, it can be observed from Examples 1 to 3 that the holes on the surface of the micro-arc oxidation coating formed by doping Ce salts are significantly different, the number of holes is small, and the pore size is significantly increased. From Example 1 to Example 3, the concentration of Ce salt gradually increases, the number of holes gradually decreases, and the pore size gradually increases. On the one hand, since Ce salt changes the physical properties of the electrolyte, the growth voltage of the coating increases significantly. On the other hand, the physical phase of the formed coating changes. In addition to the main phase Al2O3, there are more metal salts. This leads to a change in the difficulty of the coating being broken down to form a discharge. The more complex physical phase and higher voltage cause the coating to preferentially break down in a weak position of local unevenness to form a discharge channel. It is worth noting that there are a large number of fillers inside the holes on the surface of the coating doped with Ce salt, and the internal sealing is achieved almost along the hole wall. The larger the hole, the more obvious the filling material, which is different from the added or self-generated nanoparticles reported in many literatures. This is an unprecedented micro-arc oxidation coating that achieves self-sealing holes in one step. This is mainly because the exogenous Ce phosphate generated during the discharge process is backfilled in the coating, forms a metallurgical bond with the generated oxide and grows inside the hole, thereby forming an effective plugging of the hole.

[0047] Figure 4 LCSM images of the coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1.

[0048] like Figure 4 As shown, Figure 4 (a) is comparative example 1, Figure 4 (b) is Example 1, Figure 4 (c) is Example 2, Figure 4 (d) is Example 3. The coating surfaces prepared in Examples 1 to 3 of the present invention and Comparative Example 1 all have uneven molten material protrusion structures, and the Ce salt content has no significant effect on the roughness of the micro-arc oxidation coating.

[0049] Figure 5It is a Tafel curve diagram of electrochemical testing of Examples 1 to 3 of the present invention, Comparative Example 1 and 2A12 aluminum alloy in 3.5wt.% NaCl solution.

[0050] like Figure 5 As shown in the figure, after the 2A12 aluminum alloy is treated with micro-arc oxidation, the corrosion potential of the coating increases from -1.322V to -1.238V in comparative example 1. With the doping of Ce salt, the corrosion potential gradually increases. The corrosion potential of Example 1 is -1.063V, the corrosion potential of Example 2 is -0.788V, and the corrosion potential of Example 3 is -0.802V. Correspondingly, the corrosion current density increases from 2.649×10 -6 A.cm -2 The values ​​were reduced to 9.546×10 -9 A.cm -2 , 2.381×10 in Example 1 -9 A.cm -2 , 2.694×10 in Example 2 -10 A.cm -2 and 3.415×10 in Example 3 -10 A.cm -2 , the maximum decrease is close to 4 orders of magnitude. It can be seen that with the doping of Ce salt, the corrosion resistance of the micro-arc oxidation coating to the aluminum alloy substrate is gradually enhanced. The self-sealing and self-healing aluminum alloy corrosion-resistant coating prepared in Example 2 has the best corrosion resistance, which indicates that the self-sealing of the melt at the weak holes effectively hinders the corrosion penetration of the salt solution to the coating. In addition, the polarization resistance of the sample usually reflects the speed of its corrosion rate. The larger the resistance, the lower the corrosion rate. Polarization resistance R p The Stern-Gear equation can be used to calculate: .

[0051] in, ꞵ a and ꞵ c are two slopes near the extreme points of the Tafel curve. It can be seen that compared with the 2A12 aluminum alloy substrate, the polarization resistance of the self-sealing and self-healing aluminum alloy corrosion-resistant coatings prepared in Examples 2 and 3 is increased by 4 orders of magnitude, indicating that the Ce salt-doped coating has better corrosion resistance.

[0052] Figure 6 It is an EDS surface scan of the interior of the scratch of the coating prepared in Example 2 of the present invention and Comparative Example 1; Figure 7 It is an EDS line scan image of the interior of the scratches of the coatings prepared in Example 2 of the present invention and Comparative Example 1.

[0053] like Figures 6 and 7 As shown, Figure 6 (a) is the EDS surface scan of the scratch inside the coating prepared in Comparative Example 1. Figure 6 (c) is an EDS scan of the interior of the scratch of the coating prepared in Example 2. Figure 7 (a) is the EDS line scan image of the scratch inside the coating prepared in Comparative Example 1. Figure 7 (c) is an EDS line scan of the inside of the scratch of the coating prepared in Example 2. The coating of Comparative Example 1 and the coating of Example 2 were artificially scratched and immersed in a 3.5wt.% NaCl solution for 336 hours to observe the corrosion of the substrate / coating interface. The corrosion morphology of the coating of Comparative Example 1 around and inside the scratch after immersion for 336 hours. Figure 6 (a) and Figure 7 As shown in (a), after the coating was scratched, severe local corrosion occurred around and inside the scratch, accompanied by a large amount of corrosion products accumulated. The corrosion products were in the form of micro-nano sized particles, and the corrosion products were Al(OH)3. The above results show that once the coating is damaged, it cannot provide any protection for the substrate, and local corrosion will accelerate the corrosion of the interface substrate. After the coating of Example 2 was immersed in the same conditions for 336 hours, it was found that there was almost no change inside and around the scratch, and no severe local corrosion occurred, showing good corrosion resistance. Figure 6 (c) and Figure 7 As shown in (c), the inside of the scratch is magnified and observed. It can be seen that a thin layer of corrosion products and a small amount of micron corrosion product flakes are attached to the smooth metal surface inside. In addition to Al and O, P and Ce elements also exist on the aluminum alloy matrix. Among them, the Al element is enriched at the edge of the scratch, and P, O and Ce are locally enriched in the coating. Combined with the morphology, it can be guessed that it is scattered coating fragments. It is worth noting that the signal collection of Ce element with a high content in the entire scratch area indicates that it is uniformly distributed. In addition to the enrichment of particles, the Ce element inside the coating scratch of Example 2 is uniformly distributed in the entire scratch area. This can be attributed to Ce. 3+ Self-healing property. When the coating is damaged, Ce released from the coating at the interface 3+ It will enter the substrate interface with the solution and react with the local OH generated by the corrosion of the Al substrate. - The reaction generates Ce hydroxide, which eventually covers the local corrosion micro-area together with Al(OH)3, and plays a corrosion protection role on the substrate. The immersion test results of the above artificial scratch coatings show that the self-sealing and self-healing aluminum alloy corrosion-resistant coating provided by the present application has self-healing properties and can provide effective active corrosion protection for the aluminum alloy substrate interface.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a self-sealing and self-healing aluminum alloy corrosion-resistant coating, characterized in that: An aluminum alloy is used as a matrix, and the aluminum alloy matrix is ​​placed in an electrolyte for micro-arc oxidation treatment; the electrolyte comprises phosphate, sodium hydroxide, disodium ethylenediaminetetraacetate and a soluble cerium salt.

2. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The concentration of the phosphate is 3-20 g·L -1 , the concentration of sodium hydroxide is 1~10g·L -1 , the concentration of disodium EDTA is 2~10g·L -1 , the concentration of soluble cerium salt is 1~20g·L -1 .

3. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The phosphate includes at least one of sodium hexametaphosphate, sodium pyrophosphate, sodium dihydrogen phosphate and sodium tripolyphosphate.

4. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The soluble cerium salt includes at least one of cerium nitrate, cerium acetate and cerium carbonate.

5. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The aluminum alloy matrix is ​​any one of 2 series aluminum alloy, 5 series aluminum alloy, 6 series aluminum alloy and 7 series aluminum alloy.

6. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The micro-arc oxidation treatment is operated in a constant current mode using an alternating current power supply, with the aluminum alloy substrate serving as an anode and the stainless steel electrolytic cell serving as a cathode.

7. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 6, characterized in that: The power of the AC power source is 10~100kW, and the current density is 2~10A·dm -2 , frequency is 200~1000Hz, duty cycle is 10~30%, and discharge time is 5~20 minutes; the temperature of the electrolyte during the micro-arc oxidation treatment is 35~45°C.

8. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 1, characterized in that: The preparation method also includes pre-treating the aluminum alloy substrate, wherein the pre-treatment includes surface polishing and cleaning.

9. The method for preparing the self-sealing and self-healing aluminum alloy corrosion-resistant coating according to claim 8, characterized in that: The cleaning is carried out under ultrasonic conditions, and the ultrasonic time is 5 to 15 minutes; the cleaning is carried out using deionized water and anhydrous ethanol in sequence.

10. A self-sealing and self-healing aluminum alloy corrosion-resistant coating prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Magnesium alloy corrosion-resistant micro-arc oxidation coating with self-repairing function and preparation method thereof

    CN116516443A

Cited By

  • Coating with in-situ plugging and active protection functions as well as preparation method and application thereof

    CN121931579A

  • Coating with in-situ plugging and active protection functions, and preparation method and application thereof

    CN121931579B

  • ADC12 cast aluminum alloy self-sealing anodic oxidation liquid and preparation and application thereof

    CN122169182A

  • Self-sealing anodizing solution for adc12 cast aluminum alloy and its preparation and application

    CN122169182B